University in an oil-dependent state economy: The future of Khuzestan higher education - Hamid Farhadi Rad (Universidad de Deusto, 2021)
Purpose of the study: The understanding of the complex world and the ability to imagine the futures is the basis for planning and decision-making. Therefore, in this research, the possible future of university in an Iranian oil-dependent economy is studied, and, the best direction for higher education in Khuzestan province is explored. — Methodology: A formative scenario writing research method is used in the current study. The participants were recruited from among Iranian higher education experts purposefully; a series of in-depth interviews including personal and focus group interviews have also been conducted to reach saturation. —Main findings: The results of the present research showed that two main factors affect Khuzestan higher education: dependency on the state economy and increasingly growing social expectation from the university. Khuzestan universities have better select one of these orientations: Conservative University, Enabler University, Adaptive University, and Developmental University. According to the findings of the study, developmental orientation is the preferred scenario for Khuzestan higher education. — Applications of this study: It is argued that the developmental university is the preferred scenario for the future of higher education in Khuzestan Province and a proposal suggests its actualization. — Novelty/originality of this study: The applied scenario-based innovative research attempts to reveal the socio-economic role of universities in societies having State-Economy such as Iran, shows all the possible main paths, and finally determines the preferred path for a specific period of time. The current probe can be directly used to lead higher education policymakers of the province and be indirectly employed to help individuals adopt general orientations in higher education, as well as students and researchers who are interested in higher education studies, especially in the field of Higher Education (HE) public policymaking. Finally identified and explained the developmental university that is compatible with Khuzestan higher education situations is another novelty of this research.